2011
DOI: 10.1097/sle.0b013e318221c3f1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy and Peristomal Infection

Abstract: The use of PA did not seem to reduce peristomal infection rates. However, minimal SI was significantly associated with reduction of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Patients requiring PEG have a high mortality rate in the early period because of their comorbidities and underlying diseases. In studies predicting a 30-day mortality rate, the results were as follows: (19,20). In our study, the 3-month mortality rate was 30.9%.…”
Section: Discussionsupporting
confidence: 48%
“…Patients requiring PEG have a high mortality rate in the early period because of their comorbidities and underlying diseases. In studies predicting a 30-day mortality rate, the results were as follows: (19,20). In our study, the 3-month mortality rate was 30.9%.…”
Section: Discussionsupporting
confidence: 48%
“…Of the included articles, 27 were found to fit into the Healthcare system category 11, (with 32 citations within this category), 43 into the Individual with an ostomy category 4,5,9,12-19,22,24-28,30-32,34-37,39-57 (74 citations), and 13 into the Ostomy product category 9,10,25,39,41,55,58-64 (16 citations); several articles were found to fit into two or more categories or subcategories. The articles were divided into three evidence levels 8 : Level I (high), five articles 38,51,54,61,64 ; Level II (good), 43 articles 4,10,[12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37]41,[44][45][46][47][48][49][50]52,53,[55][56][57][58]…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The Healthcare system category included seven system level PSC risk factors related to contact, guidance and input from the healthcare system (Figure 4). In the literature review, 27 articles 11, (one Level I 38 , 24 Level II [13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , two Level III 11,23 ),…”
Section: Healthcare Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the jumping technique might be a small incision with few skin wounds, which might be correlated with the smaller wound infection rate in our study. Fagundes et al [14] recently reported that reduction in infection could be achieved not by using prophylactic antibiotics but by a minimal skin incision. In our study, irrespective of the number of levels operated, hospital stay was similar in all cases.…”
Section: Discussionmentioning
confidence: 99%